1999
DOI: 10.1046/j.1432-1327.1999.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of P‐glycoprotein‐mediated drug transport by prazosin and progesterone

Abstract: P-glycoprotein is a plasma membrane protein of mammalian cells that confers multidrug resistance by acting as a broad-specificity, ATP-dependent efflux transporter of diverse lipophilic neutral or cationic compounds. Previously, we identified two positively cooperative drug-binding sites of P-glycoprotein involved in transport [Shapiro, A. B. & Ling, V. (1997) Eur. J. Biochem. 250, 130-137]. The H site is selective for Hoechst 33342 and colchicine. The R site is selective for rhodamine 123 and anthracyclines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
217
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(231 citation statements)
references
References 30 publications
12
217
1
1
Order By: Relevance
“…The results further emphasize some of the biochemical similarities of the BeWo cells and the primary cultures of normal human cytotrophoblasts and affirm the use of the cell line for some investigations of trans-trophoblast transport of nutrients and drugs. Recent reports suggest that endogenous steroids including the hormone of pregnancy, progesterone, may regulate P-gp function [33]. Therefore, our results will form the basis for further investigation of the role of efflux systems in regulating the distribution of endogenous steroids and xenobiotics across the placenta, and their possible role in regulating P-gp function in the human trophoblast.…”
Section: Discussionmentioning
confidence: 55%
“…The results further emphasize some of the biochemical similarities of the BeWo cells and the primary cultures of normal human cytotrophoblasts and affirm the use of the cell line for some investigations of trans-trophoblast transport of nutrients and drugs. Recent reports suggest that endogenous steroids including the hormone of pregnancy, progesterone, may regulate P-gp function [33]. Therefore, our results will form the basis for further investigation of the role of efflux systems in regulating the distribution of endogenous steroids and xenobiotics across the placenta, and their possible role in regulating P-gp function in the human trophoblast.…”
Section: Discussionmentioning
confidence: 55%
“…Two or more P-gp transporter sites have been identified [38]. Verapamil, a substrate of one of the P-gp transporter sites [19] was used to determine whether methadone is a ligand of the same binding site, while progesterone binds to an allosteric modulatory site and is not transported [39].…”
Section: Discussionmentioning
confidence: 99%
“…The authors developed the nomenclature of H (Hoechst) and R (Rhodamine123) sites on the protein. Subsequent studies revealed the presence of a third (P) site that was capable of transporting prazosin [11]. In addition, these studies demonstrated that some sites are capable of binding both substrates and inhibitors.…”
Section: Introductionmentioning
confidence: 95%